MicroRNA164d suppresses the HvNAC92-HvHKT1;5 module to enhance salinity tolerance in barley - Liuhui Kuang; Hongxing Zhou; Tongtong Zhang; Fei Gao; Tao Yan; Zhong-Hua Chen; Qiufang Shen; Guoping Zhang; Lin Li; Dezhi Wu (Proceedings of the National Academy of Sciences, 2025)
Cereal crops (e.g., rice, wheat, maize, and barley) constituted the major component of global human diet and fundamentally changed human society since the dawn of agriculture around 12,000 y ago. Originated and domesticated in different continents and environments, cereal crops vary significantly in their salt tolerance. The High-Affinity K + Transporter1;5s (HKT1;5s) predominately regulate Na + accumulation and salt tolerance in salt-sensitive cereal crops by mediating shoot-to-root Na + exclusion. However, HvHKT1;5 paradoxically promotes root-to-shoot Na + translocation in salt-tolerant barley. Therefore, unravelling the regulatory mechanisms of HvHKT1;5 is critical to understanding the molecular basis of salt tolerance in barley. Here, we demonstrated that a microRNA164d-HvNAC92-HvHKT1;5 module improves salt tolerance via reduced shoot Na + accumulation and increased K + retention in barley, whereas miR164d suppresses HvNAC92 transcription factor to directly downregulate HvHKT1;5 expression. Under salinity condition, the MIR164d -OE, Hvnac92 , and Hvhkt1;5 lines showed significantly reduced root-to-shoot Na + translocation and shoot Na + content compared with the wild-type. In conclusion, we resolve the species-specific function of HKT1;5s in cereal crops by establishing miRNA-guided Na + and K + transport regulation as a regulatory framework for engineering salt-tolerant crops.